Organizational and Economic Aspects of Ensuring Information Security in Logistics Systems - A. V. Dmitriev (Управленческое консультирование)
The article discusses issues of ensuring information and economic security as one of the most important qualitative characteristics of logistics systems that determine the ability to ensure the established parameters of material ﬂows in the process of goods distribution when introducing digital systems and technologies. An analysis of modern risks and threats characteristic of the development of digital ecosystems of transport and logistics services is carried out. The key factors for ensuring economic security and their importance in logistics are examined from the point of view of ensuring operational control over compliance with established key indicators of product distribution. The issues of ensuring the parameters of commodity distribution within the established threshold values are touched upon in order to achieve optimal functioning of the commodity distribution system and ensure the economic activity of the enterprise with all the necessary resources. Logistics systems are studied for the eﬀective organization and management of material ﬂows, aimed at ensuring the reliability of operation and implementation of the strategy of economic entities. The necessity of using modern digital technologies to increase the level of economic security in logistics systems and ensure transparency, controllability and traceability of material ﬂows in the ﬁeld of commodity distribution is substantiated. At the same time, the very fact of digitalization of cargo delivery processes is considered from the perspective of the ecosystem paradigm and platform concept. The patterns of transformation of traditional logistics operators into providers of digital logistics services are substantiated. A model of a cyber-physical ecosystem in logistics has been developed, providing end-to-end management of business processes and data exchange in the process of goods distribution.